Top‐down estimate of methane emissions in California using a mesoscale inverse modeling technique: The South Coast Air Basin. Issue 13 (14th July 2015) - Cui, Yu Yan; Brioude, Jerome; McKeen, Stuart A.; Angevine, Wayne M.; Kim, Si‐Wan; Frost, Gregory J.; Ahmadov, Ravan; Peischl, Jeff; Bousserez, Nicolas; Liu, Zhen; Ryerson, Thomas B.; Wofsy, Steve C.; et al.
Abstract Methane (CH4) is the primary component of natural gas and has a larger global warming potential than CO2. Recent top‐down studies based on observations showed CH4 emissions in California's South Coast Air Basin (SoCAB) were greater than those expected from population‐apportioned bottom‐up state inventories. In this study, we quantify CH4 emissions with an advanced mesoscale inverse modeling system at a resolution of 8 km × 8 km, using aircraft measurements in the SoCAB during the 2010 Nexus of Air Quality and Climate Change campaign to constrain the inversion. To simulate atmospheric transport, we use the FLEXible PARTicle‐Weather Research and Forecasting (FLEXPART‐WRF) Lagrangian particle dispersion model driven by three configurations of the Weather Research and Forecasting (WRF) mesoscale model. We determine surface fluxes of CH4 using a Bayesian least squares method in a four‐dimensional inversion. Simulated CH4 concentrations with the posterior emission inventory achieve much better correlations with the measurements (R2 = 0.7) than using the prior inventory (U.S. Environmental Protection Agency's National Emission Inventory 2005, R2 = 0.5). The emission estimates for CH4 in the posterior, 46.3 ± 9.2 Mg CH4/h, are consistent with published observation‐based estimates. Changes in the spatial distribution of CH4 emissions in the SoCAB between the prior and posterior inventories are discussed. Missing or underestimated emissions from dairies, the oil/gas system, and landfills in the SoCAB seem to explain the differences between the prior and posterior inventories. We estimate that dairies contributed 5.9 ± 1.7 Mg CH4/h and the two sectors of oil and gas industries (production and downstream) and landfills together contributed 39.6 ± 8.1 Mg CH4/h in the SoCAB.